(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current situation and evaluate the effectiveness of health education on treatment compliance of hypertensive patients at Vinh Medical University Hospital. Research methods: Research on health education intervention on a group of subjects with comparison before and after intervention with a sample size of 96 hypertensive patients at Vinh Medical University Hospital from September 2023 until June 2024. Results: The lowest age of the research subject is 47 years old, the highest age is 92 years old; the number of people over 70 years old accounts for 51.1%; females account for a higher proportion of 60.4%; duration of illness ranges from 1 month to 10 years, the period from 1-5 years accounts for 55.1%. Before intervention, the patient’s average compliance score for hypertension treatment reached 62.3 ± 9.8 points out of a total score of 76 points. After 1 month and 2 months of intervention, patients’ compliance with hypertension treatment was significantly improved, reaching 65.6 ± 8.7 points and 69.8 ± 8.4 points. The rate of patient compliance with treatment reached 44.8% before intervention, increasing to 79.2% and 85.4% after 1 month and 2 months after intervention. Conclusion: Health education for patients to comply with hypertension treatment is very necessary and should be carried out regularly at medical facilities to improve the efficiency and quality of treatment.